Pregnant and Postpartum Women's Experiences and Perspectives on the Acceptability and Feasibility of Copackaged Medicine for Antenatal Care and PMTCT in Lesotho. (16th November 2015) - Gill, Michelle M.; Hoffman, Heather J.; Tiam, Appolinaire; Mohai, Florence M.; Mokone, Majoalane; Isavwa, Anthony; Mohale, Sesomo; Makhohlisa, Matela; Ankrah, Victor; Luo, Chewe; Guay, Laura
Abstract : Objective. To improve PMTCT and antenatal care-related service delivery, a pack with centrally prepackaged medicine was rolled out to all pregnant women in Lesotho in 2011. This study assessed acceptability and feasibility of this copackaging mechanism for drug delivery among pregnant and postpartum women. Methods. Acceptability and feasibility were assessed in a mixed method, cross-sectional study through structured interviews (SI) and semistructured interviews (SSI) conducted in 2012 and 2013. Results. 290 HIV-negative women and 437 HIV-positive women (n = 727 ) participated. Nearly all SI participants found prepackaged medicines acceptable, though modifications such as size reduction of the pack were suggested. Positive experiences included that the pack helped women take pills as instructed and contents promoted healthy pregnancies. Negative experiences included inadvertent pregnancy disclosure and discomfort carrying the pack in communities. Implementation was also feasible; 85.2% of SI participants reported adequate counseling time, though 37.8% felt pack use caused clinic delays. SSI participants reported improvement in service quality following pack introduction, due to more comprehensive counseling. Conclusions. A prepackaged drug delivery mechanism for ANC/PMTCT medicines was acceptable and feasible. Findings support continued use of this approach in Lesotho with improved design modifications to reflect the current PMTCT program of lifelong treatment for all HIV-positive pregnant women.